(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
The article focuses on the allophonic variation of consonant phonemes in phonetics and phonology. It explains how consonant phonemes are realized through different allophones depending on phonetic environment, position, and stress. The article also highlights the importance of allophonic variation for natural speech and effective pronunciation in language learning